Effect of Discharge Planning on Metabolic Factors in Type 2 Diabetic Patients - Alemeh Dehnabi; Hassan Navipour; Hamid Radsepehr; Musa al- Reza Tadayonfar (Journal of Client-centered Nursing Care, 2017)
Background: Diabetes is one of the main causes of mortality in both the developed and developing countries (e.g. Iran). It can lead to serious consequences, such as fatigue, paralysis as well as financial burden for the health system and the patients. In this research, we are going to consider the effect of discharge planning program on metabolic factors in type 2 diabetic patients. Methods: The present study is a quasi- experimental research. The samples consisted of 70 patients with type II diabetes, who were admitted to Vasei hospital in Sabzevar- Iran. The samples were selected using the convenience sampling method. Discharge planning was carried out by researchers based on the nursing process in two stages: before and after discharge. The follow- up process continued for four months after the patients’ discharge. Data collection instruments consisted of check list, medical measurement devices, sphygmomanometer, and blood test to measure metabolic factors (glycosylated hemoglobin, triglyceride, high- density lipoprotein, systolic and diastolic blood pressure and waist circumference). Data was analyzed by pair t test, independent t-test, and chi-square using SPSS-PC (V.20). Results: There was a statistically significant difference between the intervention and the control group, taking into account the average systolic blood pressure (P = 0.002), glycosylated hemoglobin (P < 0.0001), and triglycerides level (P = 0.02). However, no statistically significant difference was observed in the mean score HDL (P = 0.69), diastolic blood pressure (P = 0.3) and waist size (P = 0.46). Conclusion: According to the findings, one may conclude that the discharge planning has led to the improvement of some of the metabolic factors (glycosylated hemoglobin, triglyceride, systolic blood pressure) among the diabetic patients.